2014
DOI: 10.1002/smi.2629
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Changes in Social Relations after Earthquake Trauma among Eastern Anatolian Women: Associated Factors and Mental Health Consequences

Abstract: In this study, we examined social relations in women exposed to earthquake trauma in Eastern Anatolia, Turkey. We examined women's perceptions regarding the changes in their social relations within their neighbourhood, within their marriage and with their children; analysed the factors that were associated with these relations; and tested the hypothesis that an improvement in social relations will protect women's mental health from the negative impact of earthquake trauma. Participants consisted of a random se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 50 publications
(65 reference statements)
1
14
0
Order By: Relevance
“…The pair bond is a selective and enduring relationship between mating partners in social monogamous animals, including human beings [35]. Traumatic events deteriorate not only social relationships with friends but also marital relations [6]. Higher levels of post-traumatic stress symptoms are associated with lower couple functioning [7].…”
Section: Introductionmentioning
confidence: 99%
“…The pair bond is a selective and enduring relationship between mating partners in social monogamous animals, including human beings [35]. Traumatic events deteriorate not only social relationships with friends but also marital relations [6]. Higher levels of post-traumatic stress symptoms are associated with lower couple functioning [7].…”
Section: Introductionmentioning
confidence: 99%
“…stated that social media is a criterion for the improvement of mental well-being. [ 18 ] Some studies have noted the beneficial role of relationships,[ 10 19 20 ] mental and social care,[ 9 ] and women in the family. [ 21 ] Other important findings were social rights, access to social services, and social responsibility and commitment.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Sezgin and Punamäki, in their study on the outcome of psychological well-being on 1253 women exposed to earthquake, reported that social connections preserve women's psychological well-being against the damages of the earthquake. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…in regards to policy-making. [ 5 6 7 9 13 ] Creating mental health for each group is greatly dependent on cultural, spiritual, and social problems and follows a definition of health which includes all biopsychosocial aspects. This means that all these aspects should be considered to create the basis of mental health.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] In another study on women during Tsunami disaster in India, psychological and social care was introduced as an important and effective strategy for improving women's mental health during disasters. [ 12 ] Another study on 1253 female earthquake survivors indicated that social relations can protect women against mental health problems during earthquakes,[ 13 ] while a different study emphasized the importance of managing physical, psychological, emotional, fertility, and environmental consequences during these situations. [ 14 ] Other studies regarding health information needs of 235 nomadic women emphasized on hygiene, educational, religious, cultural, and financial needs.…”
Section: Introductionmentioning
confidence: 99%